Differences between lucid and nonlucid dream reports: a within-subjects design - Schredl, Michael; Fuchs, Carla; Mallett, Remington (Dreaming, 2022)
Lucid dreams are characterized by the awareness of the dreamer that s/he is dreaming. Typically, if the dreamer can control the dream action, pleasurable activities like flying or having sex are chosen. The present study analyzing lucid and nonlucid dream reports reported by 100 persons confirmed previous findings that lucid dreams contain more positive emotions than nonlucid dreams. Moreover, lucid dream reports also included fewer problems, being less often subject to verbal aggression, and fewer death themes. A new finding is that lucid dream reports include fewer verbal interactions and a lower number of dream characters. This would imply that lucid dreamers choose actions that often include having fun by themselves. It would be very interesting to follow up these findings with larger dream content studies and investigate dream content and emotional changes before and after becoming lucid within the same dream. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Gesehen am 26.06.2023